2020
DOI: 10.1021/acssuschemeng.0c01243
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven Direct 2,2-Difluoroacetylation Using an Organic Pigment Catalyst

Abstract: Ethyl 2-bromo-2,2-difluoroacetate reacted with alkenes during irradiation by a blue light-emitting diode (LED; 470 nm) in the presence of 10 mol % fluorescein to achieve the visible-light-driven direct 2,2-difluoroacetylation; the combination of N,N,N,N-tetramethylethylenediamine (TMEDA) as a reducing agent and 1-methyl-2-pyrrolidinone (NMP) as a solvent was essential to afford the desired 2,2-difluoroacetyl compounds, and 10 types of 2,2-difluoroalkanoates were obtained in moderate to excellent yields. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…However, pharmaceuticals with gem -difluoroallylic moieties, such as Glecaprevir, Tafluprost, and so forth, accounted for a very low proportion in known fluorine-containing pharmaceuticals, which was related to the lack of efficient synthetic approaches for such construction. , Several recent studies have focused on the synthesis of functionalized Z -allylic building blocks with gem -difluoromethylene motifs, which will undoubtedly speed up and facilitate the construction of pharmaceutically interesting molecules and advanced materials. However, the methods to access these specific skeletons are mainly finite to the semihydrogenation and diverse cross-coupling of relatives with organometallics under certain conditions (Scheme a) . Inherently, all of these strategies rely on kinetic controls and the use of specific reagents. On the other hand, photoredox catalysis with various photosensitizers has played an important role and been recognized as an efficient green process and stimulated numerous contributions of advances for the C–C bond coupling in organic synthesis in the past 2 decades. Nevertheless, not many successful cases of the photo-induced electron transfer (PET) process for the construction of organofluorine molecules have been reported yet (Scheme b,c). , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pharmaceuticals with gem -difluoroallylic moieties, such as Glecaprevir, Tafluprost, and so forth, accounted for a very low proportion in known fluorine-containing pharmaceuticals, which was related to the lack of efficient synthetic approaches for such construction. , Several recent studies have focused on the synthesis of functionalized Z -allylic building blocks with gem -difluoromethylene motifs, which will undoubtedly speed up and facilitate the construction of pharmaceutically interesting molecules and advanced materials. However, the methods to access these specific skeletons are mainly finite to the semihydrogenation and diverse cross-coupling of relatives with organometallics under certain conditions (Scheme a) . Inherently, all of these strategies rely on kinetic controls and the use of specific reagents. On the other hand, photoredox catalysis with various photosensitizers has played an important role and been recognized as an efficient green process and stimulated numerous contributions of advances for the C–C bond coupling in organic synthesis in the past 2 decades. Nevertheless, not many successful cases of the photo-induced electron transfer (PET) process for the construction of organofluorine molecules have been reported yet (Scheme b,c). , …”
Section: Introductionmentioning
confidence: 99%
“…33−39 Nevertheless, not many successful cases of the photo-induced electron transfer (PET) process for the construction of organofluorine molecules have been reported yet (Scheme 1b,c). 40,41 Herein, we report the first example of kinetic-controlled photocatalyst-free visible-light-induced stereoselective synthesis of α,α-gem-difluoro-Z-allyl ester as Z-configured gemdifluoroallylic building blocks from the reductive radical ethoxycarbonyldifluoromethylation of terminal aryl alkynes with excited Hantzsch ester (HE, diethyl 2,6-dimethyl-1,4dihydropyridine-3,5-dicarboxylate) at room temperature in moderate to excellent yields with up to Z-configuration-only stereoselectivities. The cheap and readily available BrCF 2 CO 2 Et has been employed and proven again to be a versatile and effective ethoxycarbonyldifluoromethyl radical excited Hantzsch ester has recently been identified as a strong photoreductant (*E red = −2.2 V vs SCE), which could conduct the subsequent PET process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2020, Itoh and co-workers developed a visible-light-driven direct difluoroalkylation of alkenes and alkynes by employing fluorescein, which is an organic pigment as a photo-catalyst. However, the above-mentioned methods need photo-catalysts (Scheme , eq 3) . In 2019, Fan group reported a blue-light-induced difluoroalkylation of alkynes to give hydrodifluoroalkylation products under catalyst- and oxidant-free conditions (Scheme , eq 4) .…”
Section: Introductionmentioning
confidence: 99%
“…HRMS (ESI) m/z: [M + H] + calcd for C 22 H 24 O 4 F 2 N 404.1668; found, 404.1669. . 6 After purification by silica gel column chromatography (hexane/ethyl acetate = 10:1) to give 3o (86 mg, 92%) as a colorless oil. 1 H NMR (400 MHz, CDCl 3 ): δ 7.86−7.72 (m, 4H), 4.32 (q, J = 7.2 Hz, 2H), 3.75 (t, J = 7.0 Hz, 2H), 2.20−2.08 (m, 2H), 1.94−1.82 (m, 2H), 1.34 (t, J = 7.2 Hz, 3H).…”
mentioning
confidence: 99%
“…Examples that further validate the versatility of the photocatalytic approach are the merging of titanocene­(III) and photoredox catalyses to perform the reductive ring opening of epoxides (Gansäuer et al) and the enantioselective hydroalkylation of exocyclic enones achieved by Wang et al via the combined use of the hydrogen atom transfer photocatalyst tetrabutylammonium decatungstate and chiral spiro phosphoric acids . Finally, organic dyes (e.g., fluorescein) as photocatalysts in synthesis are illustrated by the protocol for alkene difluoroacetylation described by Itoh et al Several recent innovations in photochemical synthesis involve enzymes, as reflected by the asymmetric hydrogenation of alkenes performed by means of an ene-reductase and rose Bengal co-immobilized in an alginate hydrogel (Park et al) . Cai et al reported that the reduction force obtained by the photocatalytic reduction of NAD + to NADH with carbon nitride-based photocatalysts could drive the alcohol dehydrogenase effectively in the conversion of furfural to furfuryl alcohol .…”
mentioning
confidence: 96%